Exits From Pegged Regimes : An Empirical Analysis - Otker, Inci (IMF Working Papers; Working Paper ;, 2003)
Using countries' de facto exchange rate regimes during 1985-2002, this paper analyzes the determinants of exits from pegged regimes, where exits involve shifts to more or less flexible regimes, or adjustments within the existing regime. Distinguishing episodes characterized by "exchange market pressure" from orderly exits, the estimated probabilities of alternative exit episodes indicate that crises are preceded by a deterioration of economic conditions. In contrast, orderly exits to less flexible regimes are preceded by long regime duration, a decline in financial liabilities of the banking system, and an increase in official reserves. Exits to more flexible regimes are associated with both emerging market and other developing countries, and an increase in trade openness and government borrowing from banks. The results are robust to alternative sensitivity analyses and have reasonable predictive performance, confirming that economic and financial conditions and regime duration play important roles in determining the future course of exchange rate regimes.